Genetic evaluation of guide dogs in the UK - Evans, Katharine M (2015)
Guide Dogs is the largest assistance dogs charity providing mobility support for people who are blind or partially sighted. Approximately 70% of dogs bred become working guide dogs, and this value is high compared with other guide dog schools. However, it is still desirable to increase further the proportion of dogs that are bred which successfully become guide dogs. This study aimed to complete a thorough genetic evaluation of Guide Dogs’ programme and colony to investigate the potential for using quantitative genetic tools in service of this aim.